Strength, power, speed, and agility of women basketball players according to playing position - Delextrat, A.; Cohen, D. (The Journal of Strength and Conditioning Research, 2009)
The aim of the present study was to investigate the effect of playing position on strength, power, speed, and agility performances of women basketball players. Thirty subjects playing at national level participated in this study. They were divided into 3 groups according to playing position: guards (positions 1 and 2), forwards (positions 3 and 4), and centers (position 5). Each subject performed 8 tests presented in a random order: The 30-second Wingate Anaerobic test (WAnT), isokinetic testing of the knee extensors, 2 types of jump tests, a 20-m sprint, the agility T-test, a suicide run, and a basketball chest pass. Statistical differences between playing positions were assessed using a 1-way analysis of variance (ANOVA) and Scheffe post hoc analyses. Results showed that guards performed significantly better than centers for the relative peak and mean power achieved during the WAnT (+13% and +16.9%, respectively), relative peak torque of knee extensors (+19.5%), single-leg jump (+21.8), suicide run (+7.5%), and agility T-test (+6.4%, p < 0.05). In addition, guards achieved significantly better performances than forwards in the suicide run test (+7.1%) and forwards were characterized by a greater peak torque of the knee extensors compared to centers (+22.1%). These results indicate that specific fitness training must be undertaken according to playing position. The ability to perform the suicide run, the single-leg jump, and the different movements involved in the agility T-test must be developed in guards. In contrast, speed over short distances and strength development of lower body and upper body should be performed by all playing positions.